The effect of 8 weeks of exercise training in hypoxia and normoxia on irisin levels and insulin resistance index in overweight men - mohammad azizi; Worya Tahmasebi; Peyman Mohammadi (Shahid Beheshti University, 2021)
Purpose: The prevalence of obesity as a health problem is known in all over the world, as well as diseases associated with obesity, including insulin resistance, metabolic syndrome, type 2 diabetes, high blood pressure and cardiovascular disease has spread. The purpose of this study was to evaluate the effect of exercise training in hypoxia and normoxia on irisin levels and insulin resistance index in overweight men Methods: fourteen non-athlete men divided in either hypoxic (14% oxygen) (mean age 22 ± 1.63 yr and BMI 28.48 ± 1.28 kg/m2) or normoxic (21% Oxygen) (mean age 22.14 ± 1.34 yr and BMI 27.83 ± 2.42 kg/m2) condition randomly. Subjects do aerobic training for eight weeks (each session was 45 minutes, 3 d•wk−1, with 60% VO2max). Subjects performed an exhaustion test to determine the maximum oxygen consumption before the beginning of the training. Blood samples were collected 24 hours before and after the test. Dependent t-test, independent t-test and Pearson correlation test with significant level (P≤0.05) was used to examine the hypotheses. Results: The result showed a significant increase in irisin level after eight weeks of aerobic training in both normoxia (8%) and hypoxia (12%) conditions, while the HOMA-IR had a significant reduction (P≤0.05); it has to be mentioned that no significant difference has been observed between groups in both irisin and HOMA-IR changes. Conclusion: Training in both normoxia and hypoxia conditions, through a favorable impact on irisin levels and insulin resistance and can act as an effective factor to improve the complications in overweight men.